GPS-tracking reveals annual variation in home-range and sedentary behaviour in Common Kestrels breeding in central Italy (Avocetta, 2022)
We studied the movements of Common Kestrels Falco tinnunculus in central Italy by GPS-tracking 10 individuals between 2019 and 2021. Our aim was to investigate the extent of movements during the breeding and non-breeding seasons. In the breeding season the mean home-range size increased from incubation (1.11 km2) to the chick-rearing period (3.35 km2), and the average home-range for the entire study period was 3.68 km2. In winter, all tagged individuals remained within a few hundred meters of their nesting area, revealing for the first time a non-migratory behaviour for the species. In conclusion, our study provides novel data on the movement ecology of Kestrels during both the breeding and non-breeding seasons, and documented the resident behaviour of Kestrels in central Italy.
Keywords: home-range; GPS tracking; Kestrel; raptor migration; nest boxes; power lines